PENEGAKAN HUKUM PIDANA PUNGUTAN LIAR DALAM PROSES REKRUTMEN DI PT GLOSTAR INDONESIA - Sulpia Apipah, Nenden (Truth de Journal, 2025)
Illegal levies in the recruitment process are a form of abuse of authority that violates the law and harms job seekers. This study aims to examine the enforcement of criminal law against illegal levy practices in PT Glostar Indonesia, Sukabumi Regency. To achieve this goal, this study uses an empirical juridical method, which combines normative analysis with field data obtained through in-depth interviews with victims and police officers, as well as direct observation. The results of the study show that there is a practice of illegal levies, where intermediaries ask for money between IDR 5 million to IDR 8 million from job seekers. Legally, this action meets the elements of the Crime of Extortion and Fraud (Articles 368 & 378 of the Criminal Code) and has the potential to be a Crime of Corruption (Article 12 letter e of the Corruption Law). However, law enforcement obstacles include a lack of reports from victims, weak internal company supervision, and a permissive community culture. Nevertheless, the existence of the Saber Pungli Task Force and increasing public awareness are key elements in the eradication of pungli, emphasizing the importance of supervision and protection for victims.